2023
DOI: 10.1177/03635465221145697
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Magnetic Resonance Imaging in the Diagnosis of Multiple Ligament Knee Injuries: A Multicenter Study of 178 Patients

Abstract: Background: Magnetic resonance imaging (MRI) has shown limited diagnostic accuracy for multiple ligament knee injuries (MLKIs), especially posterolateral corner (PLC) injuries. Hypothesis: The diagnostic accuracy of MRI for MLKIs will only be moderate for some knee structures. Patient-related factors and injury patterns could modify the diagnostic accuracy of MRI. Study Design: Cohort study; Level of evidence, 3. Methods: All patients with MLKIs surgically treated between January 2014 and December 2020 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Rakhra et al found a high accuracy of MRI for detecting tears of the PLC components (lateral collateral ligament, biceps femoris tendon, PT and posterolateral ligamentocapsular complex), ranging from 82% to 95% in multiligament‐injured knees but did not evaluate the PFL as a separate structure [ 29 ]. In a large study evaluating 178 MRIs in patients with multiligamentous knee injuries, the reporting percentage of the PFL was only 47.8% [ 32 ]. The diagnostic accuracy, however, was 80.7%, equal to that of the LCL, but the LCL had a reporting percentage of 94.9%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rakhra et al found a high accuracy of MRI for detecting tears of the PLC components (lateral collateral ligament, biceps femoris tendon, PT and posterolateral ligamentocapsular complex), ranging from 82% to 95% in multiligament‐injured knees but did not evaluate the PFL as a separate structure [ 29 ]. In a large study evaluating 178 MRIs in patients with multiligamentous knee injuries, the reporting percentage of the PFL was only 47.8% [ 32 ]. The diagnostic accuracy, however, was 80.7%, equal to that of the LCL, but the LCL had a reporting percentage of 94.9%.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic accuracy, however, was 80.7%, equal to that of the LCL, but the LCL had a reporting percentage of 94.9%. The positive predictive value of the PFL in the study by Sanchez‐Munoz et al was 80.8%, almost equal to that of the medial collateral ligament (MCL), but the MCL had a reporting percentage of 99.4% [ 32 ]. McKean et al found a sensitivity for visualization of the PFL of 90% and they mention that routine review of the PLC and PFL should be an essential part of acute knee imaging [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recommend reporting ligament pathology as full-or partial-thickness tears, bearing in mind the limitations of MRI in diagnosing partial tears [6,26,27]. Searching for indirect signs of ligament insufficiency or deficiency as well as evaluation of joint malalignment may increase confidence in diagnosis [23,25].…”
Section: Ligaments and Capsular Structuresmentioning
confidence: 99%
“…Once considered the "dark side" of the knee, understanding of the anatomy and biomechanics of the posterolateral corner (PLC) was originally limited, resulting in poor diagnostic capabilities and limited treatment options in patients sustaining PLC injuries [5,6]. However, an advanced understanding of the biomechanical role of each anatomic structure comprising the PLC, along with recent investigations correlating physical examination findings with specific anatomic deficiencies, coupled with improvements in diagnostic imaging [22,44], have resulted in increased awareness and diagnosis of PLC injuries [23,36,40,41,48]. PLC injuries are commonly associated with injuries to the anterior cruciate ligament (ACL) and/or posterior cruciate ligament (PCL), with only 28% of PLC injuries reported to occur in isolation [5,11].…”
Section: Introductionmentioning
confidence: 99%